Electronic Commerce Adoption in Australia and New Zealand - Ratnasingam, Pauline (Malaysian Journal of Computer Science, 2001)
This paper presents the findings of research relating to electronic commerce adoption in the Asia-Pacific region (particularly in Australia and New Zealand). A survey questionnaire was used to gather opinions about the current status of electronic commerce in Australian and New Zealand organizations. The joint mail/web survey was conducted between September 1998 and February 1999. The focus of the survey was to investigate potential benefits of electronic commerce, potential barriers and risks in electronic commerce, and expectations regarding evolution of electronic commerce. The findings were compared with data from similar research carried out in Europe around the same time. Based upon the findings of the survey, recommendations for increasing the adoption rate of electronic commerce are presented.